2021
DOI: 10.1021/jasms.0c00463
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Dynamics of α-Synuclein during the Interaction with Phospholipid Nanodiscs by Millisecond Hydrogen–Deuterium Exchange Mass Spectrometry

Abstract: Both normal and pathological functions of αsynuclein (αSN), an abundant protein in the central and peripheral nervous system, have been linked to its interaction with membrane lipid bilayers. The ability to characterize structural transitions of αSN upon membrane complexation will clarify molecular mechanisms associated with αSN-linked pathologies, including Parkinson's disease (PD), multiple systems atrophy, and other synucleinopathies. In this work, time-resolved electrospray ionization hydrogen/deuterium ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 105 publications
3
7
0
Order By: Relevance
“…The study observed that global refolding corresponding to the formation of secondary structural elements occurred relatively late in the pathway at 10 s. 200 Finally, work from Oganesyan, Wilson, and co-workers explored the changes in conformational dynamics associated with the interaction between alpha-synuclein (a Parkinson's-linked protein) and lipid nanodiscs with different compositions. 201 The results were mostly confirmatory of previous NMR-based studies on this system but were nonetheless the first application of timeresolved HDX-MS to characterize protein lipid nanodisc interactions, and they provided critical orthogonal support for proposed mechanisms of pathogenic alpha-synuclein aggregation in this challenging system.…”
Section: Lipid Binding and Membrane Proteinssupporting
confidence: 77%
“…The study observed that global refolding corresponding to the formation of secondary structural elements occurred relatively late in the pathway at 10 s. 200 Finally, work from Oganesyan, Wilson, and co-workers explored the changes in conformational dynamics associated with the interaction between alpha-synuclein (a Parkinson's-linked protein) and lipid nanodiscs with different compositions. 201 The results were mostly confirmatory of previous NMR-based studies on this system but were nonetheless the first application of timeresolved HDX-MS to characterize protein lipid nanodisc interactions, and they provided critical orthogonal support for proposed mechanisms of pathogenic alpha-synuclein aggregation in this challenging system.…”
Section: Lipid Binding and Membrane Proteinssupporting
confidence: 77%
“…These data indicate that free α-syn can bind zwitterionic lipids to a small degree, but α-syn does not directly associate with the zwitterionic membrane surface. Prior research has also observed minimal interactions with zwitterionic lipids. , …”
Section: Results and Discussionmentioning
confidence: 92%
“…Prior research has also observed minimal interactions with zwitterionic lipids. 45,46 In contrast, α-syn directly associated with anionic DMPG nanodiscs. Macromolecular mass defect analysis revealed the stoichiometry of associations of α-syn with DMPG nanodiscs (Figure 1D,E) as 0:1, 1:1, and 2:1 α-syn:nanodisc at lower concentrations.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…Due to its rapidly interconverting conformations, the structural dynamics of monomeric aSyn is intractable by most structural biology techniques. Hydrogen/deuterium-exchange mass spectrometry (HDX-MS) is one of the few techniques capable of capturing such conformational information on aSyn at high structural resolution. , Previous studies on aSyn using HDX-MS have shown that it exchanges on the millisecond timescale and as such requires specialized instrumentation. , Here, we obtained data at high structural and temporal resolution for the aSyn monomer under physiologically relevant solution conditions. This was achieved by HDX-MS on the millisecond timescale coupled with a gas-phase “soft fragmentation” technique, electron-transfer dissociation (ETD).…”
Section: Introductionmentioning
confidence: 99%
“… 16 , 17 Previous studies on aSyn using HDX-MS have shown that it exchanges on the millisecond timescale and as such requires specialized instrumentation. 18 , 19 Here, we obtained data at high structural and temporal resolution for the aSyn monomer under physiologically relevant solution conditions. This was achieved by HDX-MS on the millisecond timescale coupled with a gas-phase “soft fragmentation” technique, electron-transfer dissociation (ETD).…”
Section: Introductionmentioning
confidence: 99%